Through the Students’ Lens: Perceptions of Emotional Intelligence Informed Instruction and Communicative Engagement - Adella Fita Amarsa Kasablanca; Yanuarius Yanu Dharmawan; Bayu Andika Prasatyo (Universitas PGRI Pontianak, 2026)
Emotional factors significantly dictate the success of English Language Learners (ELLs) in navigating cognitively demanding tasks. While Emotional Intelligence (EI) is widely linked to academic achievement, its practical application as a deliberate instructional resource within specific local Indonesian contexts remains under-examined. (Objective) This case study aims to investigate how students perceive the development of core EI skills encompassing self-awareness, self-regulation, motivation, empathy, and social skills and how these perceptions shape their communicative engagement at Homey English. Employing a qualitative study design, data were collected through a questionnaire distributed to 25 ELLs, supported by classroom observations to assess learners' emotional responses and interaction patterns during EI-informed instruction. The findings revealed that most students exhibited high self-awareness and strong empathy, which directly contributed to increased self-esteem and supportive peer networks. However, self-regulation yielded moderate results, with only 34.6% of students fully able to handle academic stress, indicating that managing impulsivity requires explicit pedagogical intervention. Furthermore, learners demonstrated stable motivation and a high preference for collaborative problem-solving. These results imply that integrating explicit, context-sensitive EI routines into language instruction effectively minimizes the affective filter. By addressing emotional needs, teachers can foster a more resilient, interactive, and psychologically safe environment that significantly enhances learners' willingness to communicate.